1988
DOI: 10.3146/i0095-3679-15-2-12
|View full text |Cite
|
Sign up to set email alerts
|

Selection Among Early Generation Peanut Progeny for Enhanced Nitrogen Fixation1

Abstract: Recurrent selection provides an established methodology for host improvement which should be applicable to increasing N, fixation. This study was conducted to evaluate response to three cycles of phenotypic selection for fresh plant weight, nodule number and dry weight, and acetylene reduction when individual peanut (Arachis hypogaea L.) plants were evaluated in the greenhouse using a mixture of four Bradyrhizobium strains as inoculum. The F, generation derived from a single cross, Florigiant x CES 101, consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Similar results of relatively low h 2 b estimates for NN have been observed in other studies (Pimratch et al, 2004b;Phudenpa et al, 2005). Arrendell et al (1988) also reported very low realized heritability estimates for NN (0.05) and NDW (0.06). Cruickshank et al (2004) reported that the heritability estimates varied signifi cantly between crosses and traits depending on levels of genetic variation in parents.…”
Section: Resultsmentioning
confidence: 96%
“…Similar results of relatively low h 2 b estimates for NN have been observed in other studies (Pimratch et al, 2004b;Phudenpa et al, 2005). Arrendell et al (1988) also reported very low realized heritability estimates for NN (0.05) and NDW (0.06). Cruickshank et al (2004) reported that the heritability estimates varied signifi cantly between crosses and traits depending on levels of genetic variation in parents.…”
Section: Resultsmentioning
confidence: 96%